Psychotropic Medication Use and Changes During Hospitalization for Older Adults Living With Dementia. (June 2023) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Kuzmik, Ashley; Drazich, Brittany; McPherson, Rachel; Kim, Nayeon; Wells, Chris; Zhu, Shijun
To describe the use of psychotropic medications among older hospitalized patients. This was a descriptive study using baseline data from the first 308 older patients in a function focused care intervention study. Age, gender, race, comorbidities, admitting diagnosis, and medications (antidepressants, antianxiety medications, anticonvulsants, dementia drugs, antipsychotics, sedative-hypnotics, and opioids) were obtained at baseline and discharge. To compare change over time, generalized estimating equations were used. Participants were mostly female (63%) and White (69%) and were 83.1 years old on average. Antidepressant, antianxiety, anticonvulsant, dementia medication, sedative-hypnotic, and opioid use remained essentially unchanged between admission and discharge. Antipsychotic medication use increased significantly from 16% to 21% at discharge. There was persistent use of psychotropic medication among hospitalized older adults living with dementia and little evidence of deprescribing. There was some indication of changes made during hospitalization that may be appropriate, even without a focused deprescribing initiative.